ANALYSIS OF THE IMPACT OF EDUCATION POLICY IN THE SOCIETY 5.0 ERA ON IMPROVING THE QUALITY OF NATIONAL DEVELOPMENT IN JEMBER - Atho'a Rosfalia, Nihna; Durrotun Nasikhah, Ikha; Priyo Suhasto, Firman; Anis Zulaiha, Mailinda (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
This study aims to analyze the influence of education policies in the Society 5.0 era on improving the quality of national development, with a focus on high school and vocational high school (SMA) levels in Jember Regency. The research approachemployed a mixed methods approach, including surveys, in-depth interviews, and observations of students, teachers, and principals. The research findings indicate that technology-based education policies contribute to improving students' digital literacy , strengthening their character, and improving the readiness of educational institutions. Despite infrastructure gaps between regions, the majority of schools have initiated the shift toward technology-based learning. Teachers play a crucial role asdrivers of change, although ongoing training and a relevant curriculum are still needed. In addition to strengthening soft skills , In addition to digital skills and ethics, Society 5.0 education also encourages students to engage in local development through social projects, digital entrepreneurship, and cultural preservation. The study concluded that the successful implementation of Society 5.0 in education depends heavily on policy synergy, school readiness, and active student participation. Recommendations focus on strengthening teacher capacity, equitable distribution of facilities, and collaboration between educational institutions, the government, and the industrial sector to enhance education's role in national development.